Uptake of Nitrobenzylthioinosine and Purine β-l-Nucleosides by Intracellular Toxoplasma gondii - Al Safarjalani, Omar N. (American Society for Microbiology, 2003)
Intracellular Toxoplasma gondii grown in human foreskin fibroblast cells transported nitrobenzylthioinosine {NBMPR; 6-[(4-nitrobenzyl)mercapto]-9-β-d-ribofuranosylpurine}, an inhibitor of nucleoside transport in mammalian cells, as well as the nonphysiological β-l-enantiomers of purine nucleosides, β-l-adenosine, β-l-deoxyadenosine, and β-l-guanosine. The β-l-pyrimidine nucleosides, β-l-uridine, β-l-cytidine, and β-l-thymidine, were not transported. The uptake of NBMPR and the nonphysiological purine nucleoside β-l-enantiomers by the intracellular parasites also implies that Toxoplasma-infected cells can transport these nucleosides. In sharp contrast, under the same conditions, uninfected fibroblast cells did not transport NBMPR or any of the unnatural β-l-nucleosides. β-d-Adenosine and dipyridamole, another inhibitor of nucleoside transport, inhibited the uptake of NBMPR and β-l-stereoisomers of the purine nucleosides by intracellular Toxoplasma and Toxoplasma-infected cells. Furthermore, infection with a Toxoplasma mutant deficient in parasite adenosine/purine nucleoside transport reduced or abolished the uptake of β-d-adenosine, NBMPR, and purine β-l-nucleosides. Hence, the presence of the Toxoplasma adenosine/purine nucleoside transporters is apparently essential for the uptake of NBMPR and purine β-l-nucleosides by intracellular Toxoplasma and Toxoplasma-infected cells. These results also demonstrate that, in contrast to the mammalian nucleoside transporters, the Toxoplasma adenosine/purine nucleoside transporter(s) lacks stereospecificity and substrate specificity in the transport of purine nucleosides. In addition, infection with T. gondii confers the properties of the parasite's purine nucleoside transport on the parasitized host cells and enables the infected cells to transport purine nucleosides that were not transported by uninfected cells. These unique characteristics of purine nucleoside transport in T. gondii may aid in the identification of new promising antitoxoplasmic drugs.